Perception of Lagos Health Workers on the Influence of COVID 19 Vaccine Frames in the Print Media (Journal of Management and Social Sciences, 2023)
This study investigated how COVID-19 vaccine frames in print media influence the perceptions of health workers at Infectious Disease Hospital Lagos (IDHL). Using a survey method, a sample of 161 respondents was generated from a population of 270 health workers at IDH, based on Taro Yamani’s formula. The study, which was anchored on framing theory, found that health workers at IDHL were influenced by the print media's COVID-19 vaccine frames, with an overall result of 47% (M=2.49,SD=1.28). Furthermore, the study revealed that more than half (65.48%) of the infectious disease health workers in Lagos perceived COVID-19 vaccine frames in print media, as shown by their mean (M=3.27, SD=1.17). The research concluded that print media frames of COVID-19 vaccines can have desirable effects on perceptions that fuel vaccine hesitancy, as well as promote desirable health perceptions that can increase vaccine uptake. However, media frames that provoke fear can indirectly instil fear in people, preventing them from taking the vaccines. Therefore, the study recommends that the print media assume more social responsibility roles in health promotion through media framing.